Traditional ecological knowledge among Sami reindeer herders in northern Sweden about vascular plants grazed by reindeer - Inga, Berit; Danell, Öje (Rangifer, 2013)
Traditional knowledge about how reindeer utilize forage resources was expected to be crucial to reindeer herders. Seventeen Sami reindeer herders in four reindeer herding communities in Sweden (“samebyar” in Swedish) were interviewed about plants species considered to be important reindeer food plants in scientific literature. Among 40 plant species, which the informants were asked to identify and indicate whether and when they were grazed by reindeer, they identified a total of 21 plant taxa and five plant groups. They especially recognised species that were used as human food by the Sami themselves, but certain specific forage plants were also identified. Detailed knowledge of vascular plants at the species level was surprisingly general, which may indicate that knowledge of pasture resources in a detailed species level is not of vital importance. This fact is in sharp contradiction to the detailed knowledge that Sami people express for example about reindeer (as an animal) or snow (as physical element). The plausible explanation is that observations of individual plant species are unnecessarily detailed information in large-scale reindeer pastoralism, because the animals graze freely under loose herding and border surveillance.